Economic impact of digital dermatitis treatment on a dairy farm: an application of the break-even analysis - Akin,Ibrahim (2018)
ABSTRACT: This study aimed to evaluate the economic efficiency of DD treatment on milk yield in lame cows suffering from DD. A total of 33 Holstein dairy cows with DD were included in the study. The milk yields were assessed as (1st); beginning milk production (BMP), (2nd); peak milk production before the diagnosis (PMPBD), (3rd); diagnosis day milk production (DMP), and (4th); post-treatment milk production (TMP). In the first stage of analyses, using the E-views equity test of means program, cows were classified into three groups for diagnosis time of DD according to the day in milk (DIM) (Group 1: 0 ≤ DIM ≤ 50, Group 2: 51 ≤ DIM ≤ 100, and Group 3: 101 ≤ DIM ≤ 150). Analysis of variance (ANOVA F-Test) and the Welch F-Test were conducted to compare the means of TMP to BMP, PMPBD, and DMP. Differences between TMP and DMP were statistically significant in all three groups. In the second stage of analyses, a cost-benefit analysis was conducted to determine the break-even point for each group to cover treatment costs for increasing milk yield. The DIM of DMP was considered as the gained milk yield per cow. Treatment cost and the mean break-even DIM for each group was then calculated. After treatment, the mean optimum break-even day for Groups 1, 2, and 3 was determined as 18.68, 26.43, and 27.14, respectively. Results suggested that treatment of DD may be considered as favorable and useful for a dairy economy.